Application of High Performance Computing to Earthquake Hazard and Disaster Estimation in Urban Area - Hori, Muneo; Ichimura, Tsuyoshi; Wijerathne, Lalith; Ohtani, Hideyuki; Chen, Jiang; Fujita, Kohei; Motoyama, Hiroyuki (Frontiers in Built Environment, 2018)
Integrated earthquake simulation (IES) is a seamless simulation of analyzing all processes of earthquake hazard and disaster. There are two difficulties in carrying out IES, namely, the requirement of large scale computation and the requirement of numerous analysis models for structures in an urban area, and they are solved by taking advantage of High Performance Computing (HPC) and by developing a system of automated model construction. HPC is a key element in developing IES, as it needs to analyze wave propagation and amplification processes in an underground structure; a model of high fidelity for the underground structure exceeds a degree-of-freedom larger than 100 billion. Examples of IES for Tokyo Metropolis are presented; the numerical computation is made by using K computer, the supercomputer of Japan. The estimation of earthquake hazard and disaster for a given earthquake scenario is made by the ground motion simulation and the urban area seismic response simulation, respectively, for the target area of 10,000 $×$ 10,000 m.